Evaluation of Decentration, Tilt and Angular Orientation of Toric Intraocular Lens - Fus, Martin; Pitrova, Sarka (Clinical ophthalmology (Auckland, N.Z.), 2021)
PURPOSE: The aim of this study was to develop software for the universal objective evaluation of factors influencing intraocular correction of astigmatism, such as decentration, tilt, axial position and angular orientation the toric intraocular lens (IOL). PATIENTS AND METHODS: Software was developed using the MS Visual Studio environment. The analysis was presented using images of 67 eyes with an implanted IOLs of the SN6ATx model series. Decentration and angular position of the lens were obtained from images of the anterior segment of the eye, using a Visucam unit. Tilt was measured on tomographic images from OCT Avanti (in meridian of highest tilt and perpendicular meridian) and preoperative biometry parameters of eye (axial length, anterior chamber depth - ACD, ocular lens thickness - LT, limbus diameter and mean keratometry value) including postoperative anterior chamber depth (pACD) were measured using Lenstar LS900. RESULTS: Applying the software methodology to the evaluation of individual toric IOL parameters, the following results were obtained: mean decentration 0.25 ± 0.17 mm which was observed in 61.19% of eyes, mean misalignment to the planned axis equal to 3.8 ± 3.6 degrees, mean highest inclination equal to 3.7 ± 1.2 degrees and mean difference of pACD and ACD was equal to 1.46 ± 0.31 mm. There was only a weak nonsignificant correlation between preoperative ACD versus decentration and tilt of IOL or a weak significant correlation between preoperative LT and both decentration and misalignment of IOL. CONCLUSION: The use of the presented methodology for determining the positional parameters of the toric IOL provided comparable results with the results of recent studies. Software design can be considered as a suitable alternative to previously published techniques, with the significant advantage of the possibility of using universal input images, their graphical editing and especially the possibility of comprehensive analysis of all parameters.
Keywords: astigmatism and cataract; toric IOL axis misalignment; toric IOL centration; toric IOL tilt